KOMPATIBILITAS DISAIN : PENENTU KINERJA WAKTU PELAKSANAAN BANGUNAN GEDUNG - Bambang Endro Yuwono; Dwi Emi Lisa Yani; Achmad Waryanto (Universitas Trisakti, 2018)
The cause of most projects experiencing delays is the poor quality of the design. One indication of the low quality of design is the change in design at the construction stage. Changes in design at the time of construction cause a decrease in time performance. There have been many studies related to the quality of design, but no one has specifically linked the quality of design to the time performance of project implementation. On the other hand, indicators for measuring the quality of the design have not been the same among the researchers, so it is necessary to re-examine the indicators to measure the quality of the design so that the results reflect the quality of the design that should be. The research was carried out by combining various design quality indicators that had been used by the researchers before, which allegedly influenced the time performance of building construction. The hypothesis proposed was